Theoretical foundations of forming and evaluating the quality of higher education - Tereshchenko, Dina; Padafet, Yuliya (Національний технічний університет "Харківський політехнічний інститут", 2022)
The article summarizes the theoretical foundations of the formation and assessment of the quality of higher education. It is established that the higher education system of Ukraine is aimed at performing a number of functions: professional-economic, social, cultural-humanistic, political-ideological. The main indicators of the quality of education are determined: knowledge, skills, skills; emotional, volitional, motivational spheres of the individual, the level of development of cognitive and other interests and needs, the degree of moral, aesthetic, physical, environmental development, as well as the assimilation of the content of the subject, the degree of abstraction in the presentation of the content of the material. It is proved that the determination of education as a market category is influenced by a number of determining factors of this sphere: the presence of non-state educational institutions; the provision of commercial services of higher education in a number of areas of training; commercialization of educational services; consideration of educational services from a new perspective: not only as a social good, but also as an economic category; strengthening the role of the state as a regulatory body due to the deterioration of the quality of this type of service; the need to achieve a balance of requirements and expectations for the quality of training of personnel of all interested market parties, etc. The content of the category "quality of Higher Education Services" is clarified as the correspondence of the set of characteristics of educational activities and scientific and technological development of higher education institutions to the strategic goals of the development of the state’s higher education system and the development strategy of higher education institutions. The analysis of the state of the higher education services market allowed us to identify modern vectors of development of domestic higher education, formulate a range of problems in this area, determine the likely risks of the higher education system for the development of a number of measures aimed at improving the quality of higher education services and leveling the negative consequences of the external environment on the educational services market. However, in recent years, there has been a tendency to shift priorities towards meeting the needs of stakeholders in the level of quality of higher education services.

У статті узагальнено теоретичні основи формування та оцінки якості вищої освіти. З’ясовано, що система вищої освіти України націлена на виконання ряду функцій: професійно-економічної, соціальної, культурно-гуманістичної, політико-ідеологічної. Визначено основні показники якості освіти: знання, вміння, навички; емоційну, вольову, мотиваційну сфери особистості, рівень розвиненості пізнавальних та інших інтересів і потреб, ступінь моральної, естетичної, фізичної, екологічної розвиненості, а також засвоєння змісту освітніх компонентів, ступінь абстрагування у викладі змісту матеріалу. Доведено, що на детермінацію освіти як ринкової категорії впливає ряд визначальних факторів даної сфери: наявність недержавних освітніх установ; надання комерційних послуг вищої освіти за низкою напрямів підготовки; комерціалізація освітніх послуг; розгляд освітніх послуг з нового ракурсу: не тільки як соціальне благо, але і як економічна категорія; посилення ролі держави як регулюючого органу у зв’язку з погіршенням якості даного типу послуг; виникнення необхідності досягнення балансу вимог і очікувань якості підготовки персоналу всіх зацікавлених сторін ринку та ін. Уточнено зміст категорії «якість вищої освіти» як відповідність сукупності характеристик освітньої діяльності та науково-технологічного розвитку закладу вищої освіти стратегічним цілям розвитку системи вищої освіти держави та стратегії розвитку закладів вищої освіти. Аналіз стану ринку послуг вищої освіти дозволив виявити сучасні вектори розвитку вітчизняної вищої освіти, сформулювати спектр проблем даної сфери, визначити ймовірні ризики системи вищої освіти для розробки ряду заходів, спрямованих на поліпшення якості послуг вищої освіти та нівелювання негативних наслідків впливу зовнішнього середовища на ринок освітніх послуг. Однак в останні роки намітилася тенденція зміщення пріоритетів у бік задоволення потреб зацікавлених сторін у рівні якості послуг вищої освіти.
Теоретичні основи формування та оцінки якості вищої освіти
Keywords: higher education system; institutions of higher education; quality of education; indicators of quality of education; quality of higher education services; система вищої освіти; заклади вищої освіти; якість освіти; показники якості освіти; якість послуг вищої освіти